'We don't have the right to get sick': A qualitative study of gaps in public health insurance among Im/migrant women in British Columbia, Canada. - Shira M Goldenberg; Shaina Schafers; Maggie Hamel-Smith Grassby; Stefanie Machado; Ruth Lavergne; Mei-Ling Wiedmeyer; IRIS Study Team (Public Library of Science (PLoS), 2023)
Globally, the exclusion of im/migrants from public health care systems remains a significant health and human rights issue, calling into question claims of 'universality' of public health systems where eligibility for coverage is determined by immigration status. We aimed to describe lived experiences of health insurance coverage and the health and social impacts of gaps in health insurance amongst im/migrant women in British Columbia (BC), Canada. This analysis draws on qualitative in-depth interviews (n = 78) with im/migrant women and im/migrant-focused service providers (n = 10) conducted between July 2018-March 2021 in Metro Vancouver, BC, as part of a larger community-based, mixed-methods study of im/migrants' health access (IRIS). In contrast to common perceptions of Canada's health system as 'universal', participants faced multifaceted barriers to health insurance and necessary healthcare for themselves and their families following arrival in BC. Narratives highlighted the ways in which ineligibility for public health insurance coverage resulted in unmet needs for essential sexual and reproductive health and preventive care among im/migrant women, children, and families. Participants also described ineligibility for public health insurance as resulting in a high economic burden, and that exclusion from public health insurance perpetuated experiences of discrimination, invisibility, and exclusion from systems of care amongst im/migrant participants. Despite these structural challenges, participant narratives highlighted the crucial role of community-based supports for minimizing harm and navigating oppressive immigration and health systems. Changes to immigration and health policies are required to remove barriers to public health care for im/migrant women and ensure that Canada's health system is accessible to all. Expanding health insurance options to cover all residents and decoupling health insurance eligibility from immigration status are recommended, alongside implementation of 'Sanctuary' policies at the local level.